Kontroversi subsidi BBM dalam keuangan negara: Legitimasi dari fakra empiris - Munrokhim Misanam (Universitas Islam Indonesia, 1998)
The debate over the importance of subsidizing fuel energy still persist in nowdays. The conventional argument against the policy argues that it puts government in a difficult financial situation. While the argument for the policy argues that it supports the economy especially of the lower-income people.